Going Nowhere: the Stranger and the Pilgrim in the Journal of George Fox - Hinds, Hilary (Quaker studies, 2015)
This article examines the rhetoric and poetics of movement and stillness in early Quaker culture. George Fox urged Friends to stand still', and stillness was valued as the godly heart of the Meeting for Worship. Nonetheless, the lives of Fox and other early Public Friends were insistently peripatetic, and Fox's Journal is largely structured around accounts of his travels. How, then, might we understand the place of the journey and the rhetoric of movement in early Quaker practice and culture? By means of a close analysis of the figure of the stranger in Fox's Journal and a comparative reading of this text in relation to seventeenth-century pilgrimage literature, the article argues that early Quakerism's conception of the inward light as a unifying force reframed the meanings of travel in a way that informed both the practice and the writings of early Friends.